The eloquence of art
1 online resource.
Keywords: "For those within the fields of art history and Byzantine studies, Professor Henry Maguire needs no introduction. His publications transformed the way art historians approach medieval art through his insightful integration of rhetoric, poetry and non-canonical objects into the study of Byzantine art. His ground-breaking studies of Byzantine art that consider the natural world, magic, and imperial imagery, among other themes, have re-defined the ways medieval art is interpreted. From notable monuments to small-scale and privately-used objects, Maguire's work has guided a generation of scholars to new conclusions about the place of art and its function in Byzantium. In this volume, twenty-three of Henry Maguire's colleagues and friends have contributed papers in his honour, resulting in studies that reflect the broad range of his scholarly interests"--